Increase expression of CD177 in Kawasaki disease - Ying-Hsien Huang; Mao-Hung Lo; Xin-Yuan Cai; Shih-Feng Liu; Ho-Chang Kuo (BMC, 2019)
Abstract Background Kawasaki disease (KD) is the most common acute coronary vasculitis disease to occur in children. Its incidence has been attributed to the combined effects of infection, genetics, and immunity. Although the etiopathogenesis of KD remains unknown, we have performed a survey of global genetic DNA methylation status and transcripts expression in KD patients in order to determine their contribution to the pathogenesis of KD. Methods We recruited 148 participants for this case-control study. The chip studies consisted of 18 KD patients that were analyzed both before undergoing intravenous immunoglobulin (IVIG) treatment and at least 3 weeks afterward, as well as 36 non-KD control subjects, using Illumina HumanMethylation450 BeadChip and Affymetrix GeneChip® Human Transcriptome Array 2.0. We then carried out real-time quantitative PCR on a separate cohort of 94 subjects for validation. Results According to our microarray study, CD177, a neutrophil surface molecule, appeared to be significantly upregulated in KD patients when compared to controls with epigenetic hypomethylation. After patients received IVIG treatment, CD177 mRNA levels decreased significantly. PCR validation indicated that the CD177 expression is consistent with the Transcriptome Array 2.0 results. Furthermore, the area under the curve values of CD177 between KD patients and controls is 0.937. We also observed significantly higher CD177 levels in typical KD than in incomplete presentation or KD with IVIG resistance. Conclusion In this study, we have demonstrated the epigenetic hypomethylation and increased expression of CD177 during the acute stage of KD. Furthermore, a higher expression of CD177 in KD patients with typical presentation was associated with IVIG resistance.